Numerical Study of Impeller Trimming on a Centrifugal Pump Test Unit - R. Aurick Nugraha Prawito; Vivien Suphandani Djanali; Alif Arif Wicaksono (JMES: The International Journal of Mechanical Engineering and Sciences, 2019)
Centrifugal pumps have an essential role in various industries. Impeller trimming is often performed to optimize the pump performance at a particular operating point. Impeller trimming refers to a reduction in the impeller outer diameter and thus causes a change in the velocity triangle on the impeller of a centrifugal pump. Three-dimensional, unsteady simulations were conducted numerically using moving mesh. This centrifugal pump has a backward-curved impeller with six blades, with anouter diameter of 120 mm and an outlet angle of 10°, which will be trimmed to a diameter of 114 mm. Trimming the impeller reduced the outer diameter so that the outlet angle of the relative velocity to the tangential direction, β2, automatically changed according to the blade shape. The simulation was done by varying the pump discharge. The simulation results were compared with the experimental results. The results obtained in this study include quantitative data and qualitative data. Qualitative data was the appearance of velocity profiles, velocity vectors, and pressure contours. Meanwhile, the quantitative data were in the form of suction pressure, discharge pressure, head calculation, and hydraulic power. The comparison of the results of the numerical simulation with the experimental results have the same trend, although the simulation tended to underestimate the head and hydraulic power. A decrease in head and hydraulic power of the pump due to trimming the impeller from the lowest discharge to the highest discharge is as much as 13% to 24%.